TP012/#1420 XMT-1660: a phase 1B trial of a B7-H4 targeting antibody drug conjugate (ADC) in endometrial, ovarian, and breast cancers. (4th December 2022) - Hamilton, Erika; Chaudhry, Arvind; Spira, Alex; Adams, Sylvia; Abuhadra, Nour; Giordano, Antonio; Parajuli, Ritesh; Han, Hyo; Weise, Amy; Marchesani, Aubri; Josephs, Kate; Im, Ellie; et al.
Abstract : Objectives: Endometrial (EC) and ovarian cancers (OC) are some of the leading causes of cancer death in women. Despite therapeutic advances, many patients eventually develop resistance to available standard of care (SOC) therapies. B7-H4 is a poor prognostic factor and is overexpressed in several cancers including endometrial, ovarian, and breast. As a member of the CD28/B7 family of cell surface proteins, it promotes tumorigenesis by suppressing anti-tumor immunity XMT-1660 is a B7-H4-targeted Dolasynthen ADC with a precise, optimized drug-to-antibody ratio and a DolaLock microtubule inhibitor payload with controlled bystander effect. In the preclinical setting, XMT-1660 has demonstrated anti-tumor activity in EC and OC PDX models. Methods: The Ph1 trial includes a first-in-human dose escalation (DES) portion followed by a dose expansion (EXP) evaluating XMT-1660 in patients with EC, OC, and BC following progression on SOC. In the DES, BOIN design will be used to determine the MTD. The DES will assess safety and preliminary efficacy, and establish recommended phase 2 dose (RP2D). In the EXP portion, cohorts enrolling EC/OC, TNBC, ER+/HER2- BC, are planned and additional patients may be enrolled based on emerging data. The primary endpoints are safety and tolerability, overall response rate, disease control rate, and duration of response. Patients are not selected by B7-H4 status but baseline tumors samples are collected for retrospective analysis. The trial is currently enrolling patients. NCT05377996 Results: Trial in progress Conclusions: Trial in progress